ZEB represses transcription through interaction with the corepressor CtBP - Postigo, Antonio A. (The National Academy of Sciences, 1999)
ZEB is an active transcriptional repressor that regulates lymphocyte and muscle differentiation in vertebrates. Its homologue in Drosophila (zfh-1) is also essential for differentiation of somatic and cardiac muscle. Here, we demonstrate that ZEB and zfh-1 interact with the corepressor CtBP to repress transcription. ZEB and zfh-1, both contain the sequence PLDLS in the same region of the repressor domain, and we demonstrate that this sequence binds CtBP-1 and -2. In vertebrate species, ZEB contains two additional CtBP-like binding sites (variations of the PLDLS sequence) that also bind CtBP proteins and are required for full repressor activity. The three sites have an additive effect, and mutation of all three sites is necessary to abolish both binding to CtBP and repressor activity. Finally, we demonstrate that the interaction of CtBP with ZEB at the promoter is necessary for repressor activity.